CPA Review: Practice, Auditing, Law and Solutions (Book). - Burns, Thomas J.; Schlorff, H. Lee (The Accounting Review, 1979)
Abstract Reviews the book "CPA Review: Practice, Auditing, Law and Solutions," by Thomas D. Hubbard, Larry N. Killough and Ronald J. Patten.